The phenotypic plasticity of Glyceria fluitans growing over the water/land gradient - Kržič, Nina (Acta biologica slovenica, 2004)
The amphibious species Glyceria fluitans successfully thrives in an intermittent ecosystem Lake Cerknica, where floods alternate with dry periods.The species grows over the environmental gradient from open water to dry land. The plant's phenotypic plasticity was studied analysing anatomical, morphological, biochemical and physiological characteristics in specimens fromdifferent locations. Floating leaves were thicker, having abundant aerenchyma, lower chlorophyll a+b contents and higher chlorophyll a/b ratio. The relative amounts of total UV-B and UV-A screening compounds per leaf area were high and similar in all forms that indicated possibly saturated amounts. The measurement of fluorescence parameters revealed no disturbance in energy harvesting since the values of potential and effective photochemical efficiencies, photochemical and non-photochemical quenching were similar over the gradient.
Keywords: Cerkniško Jezero; Chlorophyll; Ecosystem; ekologija rastlin; Ekosistem; Fresh Water; Glyceria fluitans; Growth And Development; Klorofil; Plants; Rastline; rastlinstvo; Sladka voda; Ultravijolični žarki; Ultraviolet Rays